Bacterial leaf streak 1 encoding a mitogen‐activated protein kinase confers resistance to bacterial leaf streak in rice. (19th July 2021) - Ma, Zengfeng; Qin, Gang; Zhang, Yuexiong; Liu, Chi; Wei, Minyi; Cen, Zhenlu; Yan, Yong; Luo, Tongping; Li, Zhenjing; Liang, Haifu; Huang, Dahui; Deng, Guofu
Summary: Bacterial leaf streak (BLS) is a major bacterial disease of rice. Utilization of host genetic resistance has become one of the most important strategies for controlling BLS. However, only a few resistance genes have been characterized. Previously, a recessive BLS resistance gene bls1 was roughly mapped on chromosome 6. Here, we further delineated bls1 to a 21 kb region spanning four genes. Genetic analysis confirmed that the gene encoding a mitogen‐activated protein kinase ( OsMAPK6 ) is the target of the allelic genes BLS1 and bls1 . Overexpression of BLS1 weakened resistance to the specific Xanthomonas oryzae pv. oryzicola ( Xoc ) strain JZ‐8, while low expression of bls1 increased resistance. However, both overexpression of BLS1 and low expression of bls1 could increase no‐race‐specific broad‐spectrum resistance. These results indicate that BLS1 and bls1 negatively regulate race‐specific resistance to Xoc strain JZ‐8 but positively and negatively control broad‐spectrum resistance, respectively. Subcellular localization demonstrated that OsMAPK6 was localized in the nucleus. RGA4, which is known to mediate resistance to Xoc, is the potential target of OsMAPK6 . Overexpression of BLS1 and low expression of bls1 showed increase in salicylic acid and induced expression of defense‐related genes, simultaneously increasing broad‐spectrum resistance. Moreover, low expression of bls1 showed increase an in jasmonic acid and abscisic acid, in company with an increase in resistance to Xoc strain JZ‐8. Collectively, our study provides new insights into the understanding of BLS resistance and facilitates the development of rice host‐resistant cultivars. Significance Statement: A recessive bacterial leaf streak resistance gene bls1, which encodes a mitogen‐activated protein kinase (OsMAPK6), was cloned from common wild rice. The gene bls1 and its dominant allele BLS1 negatively regulate race‐specific resistance to Xanthomonas oryzae pv. oryzicola strain JZ‐8, but negatively and positively control broad‐spectrum resistance, respectively.